SPECT imaging of myocardial infarction using 99mTc-labeled C2A domain of synaptotagmin I in a porcine ischemia–reperfusion model - Fang, Wei; Wang, Feng; Ji, Shundong; Zhu, Xiaoguang; Meier, Heidi T.; Hellman, Robert S.; Brindle, Kevin M.; Davletov, Bazbek; Zhao, Ming (Nuclear medicine and biology, 2007)
The C2A domain of synaptotagmin I recognizes necrotic and apoptotic cells by binding to exposed anionic phospholipids. The goal is to explore the potential imaging utility of 99mTc-labeled C2A in the detection of acute cardiac cell death in a porcine model that resembles human cardiovascular physiology. Ischemia (20–25 min) was induced in pigs (M/F, 20–25 kg) using balloon angioplasty. 99mTc-C2A-GST ( n=7) or 99mTc-BSA ( n=2) was injected intravenously 1–2 h after reperfusion. Noninfarct animals were injected with 99mTc-C2A-GST ( n=4). SPECT images were acquired at 3 and 6 h postinjection. Cardiac tissues were analyzed to confirm the presence of cell death. Focal uptake was detected in five out of seven subjects at 3 h and in all infarct subjects at 6 h postinjection but not in infarct animals injected with 99mTc-BSA or in noninfarct animals with 99mTc-C2A-GST. Gamma counting of infarct versus normal myocardium yielded a 10.2±5.7-fold elevation in absolute radioactivity, with histologically confirmed infarction. We present data on imaging myocardial cell death in the acute phase of infarction in pigs. C2A holds promise and warrants further development as an infarct-avid molecular probe.